2018
DOI: 10.3390/app8122627
|View full text |Cite
|
Sign up to set email alerts
|

Brevinin-2 Drug Family—New Applied Peptide Candidates Against Methicillin-Resistant Staphylococcus aureus and Their Effects on Lys-7 Expression of Innate Immune Pathway DAF-2/DAF-16 in Caenorhabditis elegans

Abstract: The issue of Staphylococcus aureus (MRSA) developing a resistance to drugs such as methicillin has long been the focus for new drug development. In recent years, antimicrobial peptides, such as small molecular peptides with broad-spectrum antibacterial activity and special antibacterial mechanism, have shown a strong medicinal potential. In particular, the Brevinin-2 family has been shown to have a significant inhibitory effect against gram-positive bacteria (G+). In this study, we researched the influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In previous studies [10] , a four-day continuous determination of gene expression was then conducted in order to further study the effect of the peptides on MRSA inhibition and the effect of DAF-2/DAF-16 on the immune system of C. elegans. Brevinin-2-OA3,Brevinin-2ISb, and Brevinin-2TSa significantly up-regulated both the mRNA and protein levels of the key antimicrobial gene lys-7 in the DAF-2/DAF-16 pathway during 24-96 h. In this study ,we had firstly found in this work that Brevinin-2ISb was observed to extend the life span of infected and non-infected nematodes as well as enhance the expression of the tested immune response genes of adult worms, again suggesting an important role of Brevinin-2ISb in the positive modulation of immunity in the animals.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [10] , a four-day continuous determination of gene expression was then conducted in order to further study the effect of the peptides on MRSA inhibition and the effect of DAF-2/DAF-16 on the immune system of C. elegans. Brevinin-2-OA3,Brevinin-2ISb, and Brevinin-2TSa significantly up-regulated both the mRNA and protein levels of the key antimicrobial gene lys-7 in the DAF-2/DAF-16 pathway during 24-96 h. In this study ,we had firstly found in this work that Brevinin-2ISb was observed to extend the life span of infected and non-infected nematodes as well as enhance the expression of the tested immune response genes of adult worms, again suggesting an important role of Brevinin-2ISb in the positive modulation of immunity in the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first brevinin-2 peptide was extracted from the skin secretion of the frog, Rana brevipoda porsa, in 1992, the brevinin-2 family has gradually entered the researcher's field of vision [16] . The brevinin-2 family has noticeable inter-species and intra-species structural differences [17] . Unlike other families with obvious conserved sequences, the brevinin-2 family has four conserved amino acids (Lys15, Cys27, Lys28 and Cys33) [18] .…”
Section: Introductionmentioning
confidence: 99%